PENGARUH MODEL PEMBELAJARAN TIPE KOOPERATIF JIGSAW TERHADAP HASIL BELAJAR SISWA XI TAMAN MADYA (SMA) TAMANSISWA PEMATANGSIANTAR - Krisnawati Sitopu; Tumpal Manahara Siahaan; Anggun Tiur Ida Sinaga (JURNAL ILMIAH NUSANTARA, 2024)
This study aims to prove the effect of the jigsaw cooperative learning model on the learning outcomes of class XI Taman Madya (SMA) Tamansiswa Pematangsiantar economics students. The problem in this study is that the results of learning economics are still below the assessment criteria. Teachers have used a variety of learning models but sometimes this is not in accordance with the conditions experienced by students. The low learning outcomes in students are influenced by the lack of learning motivation where in the learning process students do not listen and pay attention when the teacher teaches, students are less focused when the learning process takes place such as being busy telling stories and doing assignments from other subjects and students are also lacking in group participation.This type of research is quantitative research. The population in this study were all students of class XI IPS Merdeka Taman Madya (SMA) Tamansiswa Pematangsiantar with a total of 102 students. The sample in this study consisted of 2 classes, namely class XI Merdeka 6 and XI Merdeka 8, with a total of 68 students. Based on descriptive analysis, it shows that the average learning outcomes of economics on employment and wages in classes that do not use the jigsaw cooperative learning model strategy are 75.30. While the average learning outcomes of students in classes that use the jigsaw cooperative model strategy are: 80. The results obtained are t count> t table (26.616)> 1.996). So based on the test criteria, it can be said that Ha is accepted, namely there is a significant influence of the jigsaw cooperative model strategy on student learning outcomes in the subject of economics, labor and wage material, class XI Ips Merdeka Taman Madya (SMA) Tamansiswa Pematangsiantar.